2021
DOI: 10.1016/j.jadohealth.2021.07.039
|View full text |Cite
|
Sign up to set email alerts
|

An Impact Analysis of the Early Months of the COVID-19 Pandemic on Mental Health in a Prospective Cohort of Canadian Adolescents

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 37 publications
1
35
0
Order By: Relevance
“…These results are seemingly not consistent with studies showing modest adverse impact of the pandemic on children and youth's mental health and wellbeing. 50 , 51 For example, in a survey of 166 grade 4 students in South Korea, Choi et al. 52 reported an increase in stress levels along with unchanged life satisfaction, underscoring the importance of high quality parent–child relationship in supporting children's mental health and wellbeing during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…These results are seemingly not consistent with studies showing modest adverse impact of the pandemic on children and youth's mental health and wellbeing. 50 , 51 For example, in a survey of 166 grade 4 students in South Korea, Choi et al. 52 reported an increase in stress levels along with unchanged life satisfaction, underscoring the importance of high quality parent–child relationship in supporting children's mental health and wellbeing during the pandemic.…”
Section: Discussionmentioning
confidence: 99%
“…Longitudinal research may also support our findings. For example, a study that evaluated differences in mental health before and during the pandemic showed that, although there was a decline in mental health indicators -including flourishingduring the initial stages of the lockdown measures, they were not significant when compared to the changes from previous years [24]. Maybe, during the pandemic, people had to adapt and learn to manage their circumstances and achieved environmental mastery and personal growth, characteristics related to flourishing [25].…”
Section: Discussionmentioning
confidence: 99%
“…Some examples of its statements are "I feel that I'm a person of worthy, at least on an equal plane with others" and "On the whole, I am satisfied with myself." After reversing five items and summing the total score, responses are classified into low [10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25], medium [26][27][28][29], and high (30-40) levels of self-esteem. In this study, this scale showed a reliability of 0.85.…”
Section: Self-esteem Scalementioning
confidence: 99%
“…Longitudinal studies with data collected prior to and shortly after the initial outbreak have reported mixed findings ( Chen et al, 2021 ; Hawes et al, 2021a ; Magson et al, 2021 ). For example, a study conducted among a longitudinal cohort of adolescents from Ontario and Québec, Canada (mean age of 14.1 years in 2018), concluded that the initial COVID-19 lockdown was not associated with elevated depression and anxiety symptoms ( Belanger et al, 2021 ). Conversely, in a sample of adolescents and young adults (aged 12 to 22 years) from Long Island, New York, Hawes and colleagues (2021a) found that symptoms of anxiety and depression increased in the period of end-of-March to mid-May as compared to pre-COVID-19 assessments.…”
Section: Introductionmentioning
confidence: 99%